New paleointensity results from rapidly cooled Icelandic lavas: Implications for Arctic geomagnetic field strength (Dataset) ... - G. Cromwell; L. Tauxe; S. A. Halldórsson (Magnetics Information Consortium (MagIC), 2021)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: New paleointensity results from rapidly cooled Icelandic lavas: Implications for Arctic geomagnetic field strength ...